Modification of Double Helical Kapiler Pipe to Reduce Temperature in a 100 Liter Capacity Freezer on the Ship - Prayogi, Urip; Felayati, Frengki Mohamad; Sugianto, Erik; Syaifuddin, Muhammad Rizal (Department of Naval Architecture - Diponegoro University, 2024)
The freezer machine is one of the tools on board and serves to maintain the temperature of food ingredients to keep it in good condition and fresh. Given the importance of this, the cooling machine is a tool that functions to make durable foodstuffs by naturally maintaining the temperature. Standard freezer machines produce temperatures only up to -15oC. Modification of the freezer machine needs to be done so that the temperature reaches a lower minus again by changing the capillary pipe from standard to double helical. The purpose of this study is to analyze the effect of double helical capillary pipes on the working performance of a 100-liter capacity freezer cooling machine using R600A refrigerant. In this study the frezzer machine was modified by replacing a single capillary pipe into a double helical. The method used is to conduct experiments to take data to determine the temperature produced and calculate the Coefficient of Performance (COP) before and after modification. The results of this study are the lowest temperature in the double helical capillary pipe variation during the three-hour test obtained a temperature in the range of -20.2oC while the standard capillary pipe obtained a temperature in the range of -14.9oC. The average COP for standard capillary pipes is greater at 2.773 compared to the COP of double helical capillary pipes which is 2.421. At double helical temperature values are cooler than standard capillary pipes. However, the disadvantage is that the COP of the double-helical capillary pipe is lower than the COP of the standard capillary pipe.